Herpes Simplex Virus Type 2 Myelitis: Case Report and Review of the Literature - Nardone, Raffaele; Versace, Viviana; Brigo, Francesco; Tezzon, Frediano; Zuccoli, Giulio; Pikija, Slaven; Hauer, Larissa; Sellner, Johann (Frontiers in Neurology, 2017)
Non-traumatic myelopathies can result from a wide spectrum of conditions including inflammatory, ischemic and metabolic disorders. Here, we describe the case of a 60-year old immunocompetent woman who developed acute back pain followed by rapidly ascending flaccid tetraparesis, a C6 sensory level and sphincter dysfunction within 8 hours. Acyclovir and steroids were started on day 2 and Herpes-simplex virus type 2 (HSV-2) was confirmed by PCR in cerebrospinal fluid. Magnetic-resonance imaging revealed a bilateral anterior horn tractopathy expanding from C2 to T2 and cervicothoracic cord swelling. Screening for paraneoplastic antibodies and cancer was negative. Neurophysiology aided in the work-up by corroborating root involvement. Recovery was poor despite early initiation of antiviral treatment, adjuvant anti-inflammatory therapy and neurorehabilitation efforts. The clinical course, bilateral affection of the anterior horns and early focal atrophy on follow-up MRI take a necrotizing myelitis potentially caused by intraneuronal spread of the virus into consideration. Further, we summarize the literature on classical and rare presentations of HSV-2 myeloradiculitis in non-immunocompromised patients and raise awareness for the limited treatment options for a condition with frequent devastating outcome.